Consumer Protection on Digital Trading Platforms: An Economic Law Perspective - Sidabariba, Burhan (PT. Anagata Sembagi Education, 2024)
The development of digital commerce has changed the pattern of modern economic interaction by presenting fast, efficient, and cross-border transactions, but behind these conveniences consumers face new vulnerabilities. Information asymmetry, misuse of personal data, and weak protection standards in electronic transactions pose significant potential losses. Law Number 8 of 1999 concerning Consumer Protection (UUPK) provides normative guarantees for consumer rights, while Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) presents legal legitimacy for electronic contracts as well as protection from fraud and misuse of data. However, the two regulations are still partially operational and have not been fully harmonious in responding to the complexity of digital trade. This study uses normative juridical methods with legislative and conceptual approaches to analyze the integration of the UUPK and the ITE Law in the context of economic law. The results of the study show that regulatory disharmonization creates legal uncertainty for consumers and business actors, so harmonization is needed that is able to ensure certainty, justice, and efficiency. Regulatory integration is expected to strengthen the digital consumer protection system, encourage public trust, and create a healthy, fair, and globally competitive digital trade ecosystem. Thus, digital consumer protection is not only a juridical dimension, but also an important strategy in national economic development